Measuring Pain-Related Behavioural Inhibition and Behavioural Activation System Responses: Further validity evidence for the Pain Responses Scale. - López-Martínez, Alicia Eva; Esteve-Zarazaga, Rosa; Sainero-Tirado, Gloria; Ramírez-Maestre, María del Carmen; Serrano-Ibáñez, Elena Rocío; De la Vega, Rocío; Day, Melissa A.; Jensen, Mark P. (Wolters Kluwer Health, 2024)
The Pain Responses Scale and its short form (PRS-SF) were recently developed to assess the affective, behavioural, and cognitive responses to pain based on the Behavioural Inhibition and Behavioural Activation Systems (BIS-BAS) model of chronic pain. The purpose of this study was to provide additional tests of the psychometric properties of the PRS-SF in a new sample of individuals with chronic pain. Sample: 190 adults with chronic non-cancer pain from Spain completed a translated version of the PRS-SF and a battery of questionnaires measuring validity criteria hypothesized the be associated with BIS and BAS activation, including measures of sensitivity to punishment, sensitivity to reward, pain intensity, pain interference, catastrophizing, and pain acceptance. Confirmatory factor analysis supported a 4-factor structure for the PRS-SF assessing despondent, escape, approach, and relaxation responses with marginal internal consistency for one scale (Relaxation) and adequate to good internal consistency for the others. The pattern of associations found support the validity of the instrument. The results provide additional support for the validity of the four PRS-SF scale scores, and the reliability of three of the scales. The PRS-SF may be used to measure BIS and BAS responses to pain to (1) provide further tests of the BIS-BAS model of chronic pain and/or (2) understand the potential mediating effects of BIS and BAS responses on the effects of psychological pain treatments to help determine which specific responses are most responsible for the benefits of treatment, and therefore which responses should be specifically targeted to enhance treatment response.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/8945
Keywords: Dolor - Aspectos psicológicos; Chronic non-cancer pain; BIS-BAS model of pain; Pain Responses Scale; Validity